Keunikan dan Daya Tarik Wisata Budaya ”Ritual Asyek” Dalam Media Film Dokumenter karya Syafriandi - Eliza, Meria; Syafran, Syafran (Journal of Tourism Sciences, Technology and Industry, 2023)
Documenter Film is an actualitation of work art that created from inspiration and ideas of the past event. Various programs of documenter film that existed in a society give information and knowledge through audio visual recorded. The benefits of documenter film is it’s capability to give constructive solution to the tourism phenomenon and local cultural uniqueness. The ritual of the Asyek dance is a sacred event that is to call the ancestral spirits. The ceremony or the ritual asyek event is done by involving special persons that has magical power usually it called by dukun (Pengasouh). The ritual asyek dance showed by actractive performance through documenter fillm media. Its created in a kind of association of pictury story telling. Kind of the performance called as art film or experiment. The combination of picture, music and sound atmosphere (noise) artistically as a main part of this event. Element of music is an important part that gives life movement which aroused someone’s emotion. The ritual of asyek dance as a cultural treasures of Sungai Penuh Jambi have an own uniqueness in a cultural tourism.